Growth promoting and health enhancing effects of aged palm sap-enriched activated biochar in broiler nutrition - Judith Nkechinyere Ohanaka; Chinwe Mary Nwogu; Ifeanyi Princewill Ogbuewu; Idorenyin Friday Etuk; Ifeanyi Charles Okoli (Journal of Agriculture and Rural Development in the Tropics and Subtropics)
This study aimed to assess the impact of aged palm sap-enriched activated biochar (AC+APS) supplementation on the growth performance, carcass yield, haematological parameters and biochemical indices of broilers. Two hundred and forty (240) male day-old Arbor Acres broiler chicks were assigned to five dietary treatment groups with six (6) replicates in a completely randomized design (CRD). The control group was fed a basal diet (A0) containing no additives. Groups A1 and A2 were fed a basal diet containing activated biochar (AC) at 0.50 and 1.00%, respectively, while groups A3 and A4 were fed a basal diet containing 0.50 and 1.00% activated biochar enriched with aged palm sap (AC+APS), respectively during an experimental period of 6 weeks. The results revealed significant (p<0.05) improvements in growth performance in 0.50% AC+APS-supplemented broilers compared to those in the AC-supplemented or control group during the finisher and overall production stages. The effect of AC and AC+APS inclusion on average daily feed intake was pronounced (p<0.05) only during the finisher (22-42 days) period. All the test groups exhibited similar (p>0.05) carcass traits to those of the control group and the treatments had no deleterious effects on organ development. Moreover, the AC+APS additive improved (p<0.05) haematopoietic processes / parameters, serum protein profiles, glucose synthesis, and decreased serum enzyme activities while increasing mineral retention in broilers compared to those in the control or AC-supplemented broilers. The 0.50% AC+APS therefore proved to be the most beneficial additive for improving productive and physiological functions in broilers and could be a useful substitute for antibiotic growth-promoting additives in poultry diets.